Selves : an essay in revisionary metaphysics - Strawson, Galen (Oxford : Clarendon Press, 2009)
Is there such a thing as the self? If so, what is it? Galen Strawson argues that if we look closely at what experience of a self is like, we may be able to work out what a self must be, if it exists. He concludes that selves do exist, but they are not what we think.
Part One: Introduction -- Part Two: Phenomenology: the local question -- Part Three: Phenomenology and metaphysics: self-experience and self consciousness -- Part Four: Phenomenology: the general question -- Part Five: Phenomenology and metaphysics: time and the experience of time -- Part Six: Metaphysics: preliminaries -- Part Seven: Metaphysics: the question of fact 1 -- Part Eight: Metaphysics: the question of fact 2.
Keywords: Metaphysics; Ontology; Phenomenology; Self (Philosophy); Self; fenomenologia; filosofia; itsetajunta; minä; ontologia (filosofia)